Private Sector Job Creation in MENA : Prioritizing the Reform Agenda - Baduel, Benedicte (IMF Working Papers; Working Paper ;, 2019)
This paper examines the extent to which firms in selected MENA countries reported being constrained by the business environment around the time of the Arab Spring and the extent to which these constraints affected their employment performance. The results suggest that small firms in MENA faced more structural constraints than similar firms in other regions. We also find that MENA firms' weaker job creation can be explained in great part by the macroeconomic environment and structural constraints. Low GDP growth, falling external competitiveness, corruption, lack of access to finance and poor access to electricity are found to explain a significant part of the lack of employment growth in MENA firms compared to their peers.